Physical Activity and Attitudes Toward Social Media Use of Active Individuals During the COVID-19 Pandemic in Saudi Arabia: Cross-Sectional Survey - AlMarzooqi, Mezna A. (Frontiers in Psychology, 2021)
Abstract Background Social media became an integral part of people’s lives because it encourages social relations, shares interests and activities and real-life connections. As quarantine and lockdown orders are prolonged, many people, as well as those physically active individuals, typically respond to this stressful condition by using social media platforms. Objective This study aimed to examine the level of physical activity of physically active individuals and their attitudes towards social media use during this COVID-19 pandemic. Methods A descriptive cross-sectional survey was conducted among physically active individuals in Saudi Arabia between June to July 2020. An online survey was employed among eligible participants who completed a self-administered questionnaire that covered reasons for physical activity, and attitudes toward social media platforms during the COVID-19 pandemic. Results Of these 323 participants, 29.1% were in the age group of 18 – 24, 66.6% were females and 67.8% were single. The proportion of participants who METs-min/week from vigorous activity <1680 was 31.9% and all of the participants follow people or page in social media related to sports teams and fitness models. The average number of hours spent on social media per day was 2.95 ± 0.90 hours. The majority of the participants showed positive attitudes towards using social media for exercise and physically activity. Of the eight variables, age, level of physical activity and the average of hours spent on social media emerged as significant predictors of attitudes towards the use of social media (P < 0.05). Conclusion The present survey results indicate adverse consequences of home quarantine as reflected by a small proportion of participants who had differences in levels of vigorous activities during COVID-19 pandemic in Saudi Arabia. Social media appears to be a key avenue to promote and disseminate health interventions to promote physical activity during this COVID-19 pandemic.